2019
DOI: 10.3389/fpsyg.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Cognitive Flexibility in the Influence of Counter-Stereotypes on Creativity

Abstract: The aim of this study is to explore the relationship between counter-stereotypes and creativity, and further explore the mechanism underlying the impact of priming counter-stereotypic information on individual creativity. More importantly, here we have proposed cognitive and emotional dual processing pathways, which may mediate the influences of counter-stereotypes on creativity. Two experiments examined how counter-stereotypes impacted creativity through the dual processing pathways. A total of 152 university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…For instance, Zuo et al (2019) found that learners’ perceptions can influence their creativity. Flipped learning strategies and self-directed learning styles can enhance learners’ creative performance ( Hsia et al, 2021 ; Shafait et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Zuo et al (2019) found that learners’ perceptions can influence their creativity. Flipped learning strategies and self-directed learning styles can enhance learners’ creative performance ( Hsia et al, 2021 ; Shafait et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fourth, cognitive flexibility mediated the effect of constructive conflict on innovative work behavior. Zuo et al (2019) found that cognitive flexibility mediated the link between counter-stereotypes and creativity. Extending their finding, this study confirmed that constructive conflict helped individuals to flexibly switch from one stimulation, manipulation or psychological mode to another when necessary and this in turn increased innovative work behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Cardom (2016), CF plays a mediating role between Cross-Race Interactions and psychological well-being, based on theoretical postulates by Crisp and Turner (2011). Brewster et al (2013) found that CF moderates the relationship between experiences of prejudice and mental health in bisexual people and, more recently, Zuo et al (2019) have identified the mediating role of CF in the influence of counter-stereotypes on creativity. In fact, in Spanish, some studies such as Angosto and Martínez (2004), Navarro andMebarak (2014), andEnesco et al (2014) have highlighted the importance of CF in interventions that seek to reduce prejudice towards stigmatized groups.…”
Section: Discussionmentioning
confidence: 99%